The Association of Sphenoidal Encephalocele and Right Anophthalmia with Septo-Optic Dysplasia: A Case Report - Erol, Fatih Serhat; Ucler, Necati; Kaplan, Metin; Yilmaz, Ilhan (Turkish Neurosurgical Soc, 2012)
Septo-optic dysplasia (SOD) is an extremely rare congenital anomaly, characterized with optic nerve hypoplasia and absence of septum pellucidum and/or pituitary dysfunction. In addition to classical findings of SOD, we report for the first time an 11-year-old boy, with encephalocele extending to the right sphenoidal sinus, right anophthalmia and normal pituitary functions. Despite all the major anomalies, the patient's presenting symptoms were very few and during the 11-year period the SDO had caused no complaints in our case. These findings show that the SOD course may be fairly benign. No neurological problem was encountered in the patient's follow-up, except headache. We believe that SOD should be kept in mind because of its rarity and the severity of its combined pathologies.
Keywords: Septo-optic dysplasia; Sphenoidal encephalocele; Anophthalmia; Congenital